DOI: 10.22215/etd/2013-07072
|View full text |Cite
|
Sign up to set email alerts
|

Inter-domain routing for tactical mobile ad-hoc networks

Abstract: A thesis subm itted to the Faculty o f G raduate and Postdoctoral Affairs in partial fulfillm ent o f the requirem ents for the degree o f M aster o f A pplied Science in Electrical and C om puter Engineering O ttaw a-C arleton Institute for Electrical and Com puter Engineering (OCIECE) D epartm ent o f Systems and Com puter Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Okundaye [9] proposed a routing solution that utilizes OSPF as a scalable routing result for an inter-domain network since it has variants that can work in both the fixed and MANET environment. They tested OSPF-MDR, a variant of OSPFv3 for MANETS and showed that after 20 minutes, the network of 200 routers running OSPF-MDR was seen to converge with all routers finding the shortest valid route to all other routers in the network.…”
Section: Related Workmentioning
confidence: 99%
“…Okundaye [9] proposed a routing solution that utilizes OSPF as a scalable routing result for an inter-domain network since it has variants that can work in both the fixed and MANET environment. They tested OSPF-MDR, a variant of OSPFv3 for MANETS and showed that after 20 minutes, the network of 200 routers running OSPF-MDR was seen to converge with all routers finding the shortest valid route to all other routers in the network.…”
Section: Related Workmentioning
confidence: 99%
“…The main concept which comes with the hierarchical design is the localization of the control and topology update messages exchange within the cluster boundary, hence significantly limiting the flooding of control messages and associated traffic across the network and reducing redundant traffic [8,17]. In addition to addressing the scalability issue in MANETs, a hierarchical configuration may be a typical design for MANETs used in specific applications and environment such as tactical networks, or emergency and disaster management teams [13,26]. The deployment of P2P applications on a hierarchical topology comes with many challenges, mainly as the nodes in physically separated clusters may be logically adjacent in the overlay.…”
Section: Motivation and Challengesmentioning
confidence: 99%
“…The above description of the network characteristics may apply to tactical networks which are hierarchical by design [13,51], or other configurations of MANETs such as emergency and disaster management applications [52].…”
Section: Scopementioning
confidence: 99%
See 2 more Smart Citations